An Exploration of Accounting in Merchandising Companies for High School Students in Jakarta, Indonesia - Emillia Sastrasasmita; Lim Raynard; Nicolas Fernando (Advances in Community Services Research, 2026)
Purpose: This Community Service Activity (PKM) was initiated in response to high school students’ limited understanding of the procedural aspects of journalizing transactions for trading companies. The program aims to enhance students’ conceptual understanding and journaling skills through an interactive, gamification-based learning approach and to increase their motivation to learn accounting. Method: The PKM was held at SMA Negeri 2 Jakarta on May 6, 2026, for 90 minutes, targeting 27 eleventh-grade students majoring in Economics and Accounting. The intervention was conducted through interactive lectures, discussions, case studies of trading company transactions, exercises in perpetual-system journalizing, and gamified quizzes. Evaluation was carried out using observation and a Likert-scale questionnaire. Results and Discussion: Before the intervention, most participants did not understand the differences between the accounting practices of service and merchandising companies, nor were they familiar with the journalizing procedures of the perpetual inventory system. The program was implemented in stages, beginning with an assessment of participants’ prior knowledge and concluding with an evaluation of their learning. The results showed an increase in students’ understanding, participation, and interest in accounting. Implications: This program helps improve the quality of accounting education in schools and can be replicated to cover a broader range of topics through ongoing support.